2016
DOI: 10.1111/1471-0528.14369
|View full text |Cite
|
Sign up to set email alerts
|

Simulation‐based team training for multi‐professional obstetric care teams to improve patient outcome: a multicentre, cluster randomised controlled trial

Abstract: 1-day, off-site, simulation-based team training did not reduce a composite of obstetric complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
85
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(90 citation statements)
references
References 48 publications
4
85
0
1
Order By: Relevance
“…A reduction in brachial plexus injury at birth was also found at a unit with regular multi-professional training on shoulder dystocia management [10]. A cluster randomized controlled trial performed in the Netherlands allocated 24 obstetric units to team training or not and no decreased rate of brachial plexus injury at birth was found in the intervention group [8]. The follow up time in that study was 1 year compared with 8 years in the present study, which might explain the diverting results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A reduction in brachial plexus injury at birth was also found at a unit with regular multi-professional training on shoulder dystocia management [10]. A cluster randomized controlled trial performed in the Netherlands allocated 24 obstetric units to team training or not and no decreased rate of brachial plexus injury at birth was found in the intervention group [8]. The follow up time in that study was 1 year compared with 8 years in the present study, which might explain the diverting results.…”
Section: Discussionmentioning
confidence: 99%
“…When it comes to improved obstetric and neonatal outcomes, only a small percentage of reports primarily addresses clinical outcomes and results are inconsistent [7]. One multicenter randomized control trial from the Netherlands showed how a one-day, off-site, simulation-based team training did not reduce obstetric complications (low Apgar score, severe postpartum hemorrhage, trauma due to shoulder dystocia, eclampsia, hypoxic ischemic encephalopathy) [8]. In contrast an Australian retrospective cohort study reported an overall improvement in some clinical outcomes (Apgar at 1 minute, umbilical cord lactate, and average length of infant’s stay in clinic) after a single day of training for the trainers at eight different maternity units [9].…”
Section: Introductionmentioning
confidence: 99%
“…Recent narrative reviews have highlighted the common elements in effective obstetric training and these include: training as a compulsory institution-led requirement; highfidelity simulation models; and multi-disciplinary attendance [51,52]. Not all training is associated with improved clinical outcomes [53,54] so training must be rigorously and robustly evaluated for real-world effects.…”
Section: Approaches To Skills Training (Heading A)mentioning
confidence: 99%
“…This is thought to be related to learning in communities of practice and normalising practice based tools, rather than the transfer of completely new skills and ideas [53]. This compare to training in central simulation centres has not been associated with improvements in clinical outcomes [54,55]. Studies specifically focussing on local obstetric emergency training in settings within the UK, Australia, the USA and Zimbabwe have identified significant improvements in real-life neonatal outcomes including reductions in low Apgar scores, hypoxic-ischaemic encephalopathy and brachial plexus injury [26,46,56,57].…”
Section: Local Versus Distance Training (Heading B)mentioning
confidence: 99%
“…In der Gesamtzahl nahmen die geburtshilflichen Komplikationen durch simulationsbasiertes Zwischenfallmanagement nicht ab. In dieser Studie nahm niemand aus den anaesthesiologischen Berufsgruppen teil und der Notfallkaiserschnitt war kein Trainingsszenario [26]. Für ihre Arbeit zur Reduktion von Zwischenfällen auf der Intensivstation haben Haerkens et al über 7200 Patienten eingeschlossen [21].…”
Section: Ergebnisseunclassified